Fictions of Desire Narrative Form in the Novels of Nagai Kafu - Snyder, Stephen (University of Hawaii Press, 2000)
Stephen Snyder examines Kafu's fiction in terms of narrative strategy, placing him squarely within some of the most important currents of literary modernism--at the nexus of Naturalism and the largely antithetical development of the modernist reflexive novel